Model Development of Positioning Strategy, Trust, Brand Image, Towards Purchase Intention in Virgin Coconut Oil Products MSMEs - Silvya L Mandey; Victor Paska Kalawat Kalawat Lengkongb; Olivia Nelwan; Vecky A.J. Masinambow; Joy Elly Tulung; Lucia Cecilia Mandey (Universitas Dharma Wacana, 2022)
The research aims to improve strategy, namely the act of designing in product offerings to consumers which include positioning strategies, Trust, Brand Image, towards purchase intentions in MSMEs of Virgin Coconut Oil products in North Minahasa. The population is small and medium enterprises for Virgin Coconut Oil (VCO) products in North Minahasa Regency. The implementation of this research obtained a theory that functions to explain, predict, and control a phenomenon, especially those related to the development of positioning, trust, brand, image strategies for purchase intentions in VCO product SMEs in North Minahasa Regency. The sample size in this study is 100 respondents. The variables in this study consist of positioning strategy indicators (X1), namely good performance, benefits, suitability, excellence, Trust (X2), namely the perception of trust in MSME virgin coconut oil products with indicators of reliability, credibility and benevolence, so for variable X3 ( Brand Image) namely recognition, reputation, affinity, loyalty. The purchase intention variable (Y) is design, patience, search. The results of research on marketing strategy and consumer behavior obtain a strategy model of positioning, trust and brand image that can be applied to MSMEs in the form of the Level of Technology Readiness for the community, especially the workforce in North Minahasa Regency..